Staphylococcus aureus Mutants Isolated via Exposure to Nonfluorinated Quinolones: Detection of Known and Unique Mutations - Roychoudhury, Siddhartha (American Society for Microbiology, 2001)
The in vitro development of resistance to the new nonfluorinated quinolones (NFQs; PGE 9262932, PGE 4175997, and PGE 9509924) was investigated in Staphylococcus aureus. At concentrations two times the MIC, step 1 mutants were isolated more frequently with ciprofloxacin and trovafloxacin (9.1 × 10(−8) and 5.7 × 10(−9), respectively) than with the NFQs, gatifloxacin, or clinafloxacin (<5.7 × 10(−10)). Step 2 and step 3 mutants were selected via exposure of a step 1 mutant (selected with trovafloxacin) to four times the MICs of trovafloxacin and PGE 9262932. The step 1 mutant contained the known Ser80-Phe mutation in GrlA, and the step 2 and step 3 mutants contained the known Ser80-Phe and Ser84-Leu mutations in GrlA and GyrA, respectively. Compared to ciprofloxacin, the NFQs were 8-fold more potent against the parent and 16- to 128-fold more potent against the step 3 mutants. Mutants with high-level NFQ resistance (MIC, 32 μg/ml) were isolated by the spiral plater-based serial passage technique. DNA sequence analysis of three such mutants revealed the following mutations: (i) Ser84-Leu in GyrA and Glu84-Lys and His103-Tyr in GrlA; (ii) Ser-84Leu in GyrA, Ser52-Arg in GrlA, and Glu472-Val in GrlB; and (iii) Ser84-Leu in GyrA, Glu477-Val in GyrB, and Glu84-Lys and His103-Tyr in GrlA. Addition of the efflux pump inhibitor reserpine (10 μg/ml) resulted in 4- to 16-fold increases in the potencies of the NFQs against these mutants, whereas it resulted in 2-fold increases in the potencies of the NFQs against the parent.